Why is d/dxe^x=e^xddxex=ex?

2 Answers
Dec 10, 2015

This follows from the definition of natural logarythm and its inverse.

Explanation:

ln e^x = xlnex=x

d/dx ln e^x = d/dx xddxlnex=ddxx

1/e^x d/dx e^x = 11exddxex=1

d/dx e^x = e^xddxex=ex

Dec 10, 2015

The "why" depends on how you've defined e^xex.

Explanation:

Define lnxlnx first

One approach is to define lnx = int_1^x 1/t dtlnx=x11tdt and
then to define exp(x)exp(x) to be the inverse of lnxlnx and,
finally, define e^x = exp(x)ex=exp(x).

In this case y=e^xy=ex if and only if lny=xlny=x.

Differentiating implicitly gets us 1/y dy/dx = 11ydydx=1.

So, dy/dx = y = e^xdydx=y=ex

Define e^xex independently of lnxlnx

Definition 1

For positive aa, define

a^x = lim_(rrarrx)a^x with r in the rational numbers
(We owe you a proof that this is well-defined.)

Then, using the definition of derivative:

d/dx(a^x) = lim_(hrarr0)(a^(x+h)-a^x)/h = lim(hrarr0)(a^x(a^h-1)/h)

We then define e to be the number that satisfies lim_(hrarr0)(e^h-1)/h = 1

With this definition we get
d/dx(e^x) = lim_(hrarr0)(e^(x+h)-e^x)/h = lim_(hrarr0)(e^x(e^h-1)/h)

= e^xlim_(hrarr0)((e^h-1)/h) = e^x

Definition 2

e^x = 1+x/1+x^2/(2*1)+x^3/(3*2*1) + x^4/(4!)+x^5/(5!)+ * * *

(n! = n(n-1)(n-2)* * * (1))
(We owe you a proof that this is well defined.)

Differentiating term by term (we owe you a proof that this is possible), we get

d/dx(e^x) = 0+1+(cancel(2)x)/(cancel(2)*1)+(cancel(3)x^2)/(cancel(3)*2*1) + x^3/(3!)+x^4/(4!)+* * *

Which simplifies to 1+x/1+x^2/(2*1)+x^3/(3*2*1) + x^4/(4!)+x^5/(5!)+ * * * which is again e^x